Aryl-NHC group 13 trimethyl complexes : structural, stability and bonding insights - Wu, Melissa Meiyi (2017)
This first aim of this thesis was to synthesize a series of new N-heterocyclic carbene group 13 metal complexes. The synthesis of the new compounds was achieved using group 13 trimethyl complexes and NHC starting materials. The species produced comprises of aluminium, gallium and indium group 13 metals. Furthermore, reactivity studies have also been carried out on the obtained NHC species with a series of electrophiles. All the structures synthesized have been fully characterized by single crystal X-ray studies, multi-nuclear NMR, IR and mass spectrometry.